Excess pneumonia and influenza death as herald wave of COVID-19 in England and Wales, United Kingdom. Issue 2 (February 2021) - Li, Chunyu; Zhang, Xingyue; Zhu, Yuchen; Lin, Qianying; Zhao, Shi; Yang, Lin; Li, Xiujun; He, Daihai; Stone, Lewi
Highlights: Excess pneumonia and influenza death showed a herald wave ahead of the wave of COVID-19 deaths in England and Wales, United Kingdom. We argue that this could be a death coding issue. Namely in the early phase, a proportion of COVID-19 deaths were classified as pneumonia of unknown type. Before and after the herald wave, the weekly pneumonia and influenza deaths were lower than the average of the previous five years (by 550 deaths per week).